2022
DOI: 10.1590/1807-3107bor-2022.vol36.0088
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of socioeconomic inequalities in self-perceived oral health

Abstract: Although there is a large body of evidence of the influence of social determinants on oral health, information on the mechanisms by which these determinants operate is poorly documented. Therefore, we aimed to investigate the pathways through which socioeconomic inequalities may influence self-perceived oral health (SPOH) in Brazilian adults. This cross-sectional study used data from the National Health Survey (NHS) of 2019, with a representative sample of adults aged 18 to 59 years (n = 65,803). The outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Psychosocial factors have been extensively investigated in relation to oral health and health inequalities [2][3][4][5]. Several studies have shown that the prolonged exposure to chronic psychosocial stress is associated with an increased risk of poor oral health in both children and adults [6].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial factors have been extensively investigated in relation to oral health and health inequalities [2][3][4][5]. Several studies have shown that the prolonged exposure to chronic psychosocial stress is associated with an increased risk of poor oral health in both children and adults [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although this SEP concept is commonly used in oral epidemiological research, the multiple ways for measuring it reflect the complexity of its attributes. SEP is one of the variables that has consistently been associated with diverse oral conditions [14][15][16][17][18] and dental pain [5][6][7][8]. Diverse studies have pointed out, e.g., to the association between tooth loss and SEP variables in China, where low school attainment and living in a rural location were linked to tooth loss [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse studies have pointed out, e.g., to the association between tooth loss and SEP variables in China, where low school attainment and living in a rural location were linked to tooth loss [14]. Data from Brazil identified an association between higher SEP and both better self-appraisal of oral Health and fewer missing teeth [15]. Just like in Chile, where severe poverty was associated with higher caries experience in primary and permanent dentitions [16], in Colombia individual and ecological SEP measures showed that low and very low SEP were associated with higher early tooth decay and untreated caries experiences [17].…”
Section: Introductionmentioning
confidence: 99%